Phosphorus Use Efficiency: Morphogenetic and Productive Responses of Brachiaria decumbens Genotypes (Syn: Urochloa decumbens) - Néstor Eduardo Villamizar Frontado; Gelson dos Santos Difante; Alexandre Romeiro de Araújo; Denise Baptaglin Montagner; Jéssica Gomes Rodrigues; Gabriela Oliveira de Aquino Monteiro; Manuel Cláudio Motta Macedo; Marislayne de Gusmão Pereira; Amanda Eunice Silva Moura; Eduardo Weisz Arze (Grasses)
This study evaluated the phosphorus use efficiency (PUE) in two genotypes and one cultivar of Brachiaria decumbens (HD1, HD4, and Basilisk) and the productive, morphogenic, and structural responses. The experimental design used was randomized blocks with five P rates (0, 13, 26, 52, and 104 mg dm−3). There was no forage × P rate interaction (p > 0.05), but the P rates affected the leaf appearance rate (TAR; p = 0.0314), leaf life span (LLS; p = 0.0207), phyllochron (PC; p = 0.0207), leaf elongation rate (LER; p = 0.0350), stem elongation rate (SER; p = 0.0109), and the number of live leaves (NLL; p = 0.0033). The LAR, LLS, and PC followed quadratic trends, increasing up to 52 mg dm−3, while the PC declined. The FLL, SER, and NLL increased linearly. HD1 had the highest final leaf length, LER, and NLL, while Basilisk had the lowest. There was an interaction for tiller population density (p = 0.0431), with increases of 0.26, 0.28, and 0.24 tillers for HD4, HD1, and Basilisk, respectively. Forage production (FP) increased with P, gaining 0.51 g of DM for each mg dm−3 of P added. The HD1 genotype showed higher FLL, LER, NLL, FP, and higher PUE than the HD4 genotype and the Basilisk cultivar. HD1 was more responsive to higher P rates for root production, indicating a greater need for nutrients to reach its productive potential. Phosphate fertilization positively influenced morphogenesis and forage production in the evaluated genotypes and cultivars. The HD1 genotype stood out in relation to the others, showed superiority in forage and root production, and demonstrated greater efficiency in the use of P, at a dose of 13 mg dm−3.